OC-087 Screen-Detected Colorectal Cancers are Associated with an Improved outcome when Compared with Interval Cancers when Matched for Stage. (4th June 2013) - Gill, M D; Bramble, M; Hull, M; Mills, S; Morris, E; Bradburn, M; Bury, Y; Parker, C; Lee, T; Rees, C
Abstract : Introduction: Colorectal cancers detected through the NHS Bowel Cancer Screening Programme (BCSP) have been shown to have a more favourable outcome compared to non-screen detected cancers. The aim of this study was to identify whether this was solely due to the earlier stage shift of these cancers, or whether there were other factors involved. Methods: A combination of a regional colorectal cancer registry (Northern Colorectal Cancer Audit Group) and the BCSP database were used to identify screen detected cancers and interval cancers (diagnosed after a negative faecal occult blood test, before the next screening round). All cancers were diagnosed between April 2007 and March 2010, within the North East of England. For each Dukes' stage, patient demographics, tumour characteristics, and survival rates were compared between the screen detected and interval cancer groups. Results: 322 screen detected cancers were compared against 192 interval cancers. Significant differences highlighted in bold, p < 0.05. Mean follow-up 32 months. Conclusion: With equivalent patient demographics and tumour characteristics, the improved survival of screen detected cancers over interval cancers for Stages C and D suggest that there may be a biological difference in the cancers in each group. Although lead-time bias may have a role, this may be related to a tumours propensity to bleed and therefore may reflect detection through current screening tests. Disclosure of Interest: None Declared